2021
DOI: 10.3390/plants10091973
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide-Resistant Invasive Plant Species Ludwigia decurrens Walter

Abstract: Ludwigia decurrens Walter is a dicotyledonous plant belonging to the family Onagraceae. It is native to Central Eastern USA but has been spreading quickly and has naturalized in aquatic and riparian ecosystems (including rice paddy fields) in many countries; therefore, it is now considered an invasive noxious weed. L. decurrens is highly competitive with rice and causes a significant reduction in rice production. The objective of the present study was to evaluate the efficacy of the herbicide penoxsulam for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Scholars have reported that L. decurrens reduces the development of rice plant tillers, panicles, leaves, and spikelets, according to Pessu and Umeozor [19]. As a result, there is a considerable likelihood of an economic impact due to poorer crop yields and quality [20]. The Scrophuliaceae family includes Bacopa floribunda.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have reported that L. decurrens reduces the development of rice plant tillers, panicles, leaves, and spikelets, according to Pessu and Umeozor [19]. As a result, there is a considerable likelihood of an economic impact due to poorer crop yields and quality [20]. The Scrophuliaceae family includes Bacopa floribunda.…”
Section: Introductionmentioning
confidence: 99%
“…Aplikasi herbisida dapat menekan pengaruh negatif gulma pada tanaman kentang (Barbaś et al 2020;Jabran et al 2023;Kalkhoran et al 2021). Akan tetapi penggunaan herbisida terus menerus dan dalam jangka waktu yang panjang dapat menyebabkan timbulnya resistensi gulma terhadap herbisida (Kurniadie et al 2021;Piasecki et al 2020;Rahmadi, 2021;Vulchi et al 2022), gangguan kesehatan lingkungan (He et al 2019;Hong et al 2022;Kwonpongsagoon et al 2021), bahkan dapat membahayakan organisme non target seperti koloni lebah (Macri et al 2021) dan organisme laut (Matozzo et al 2020;Sylwestrzak et al, 2021).…”
unclassified